Fake News - Andreas Grunewald; Matthias Kräkel (Institute of Labor Economics (IZA), 2017)
In the last decade, social media and the Internet have amplified the possibility to spread false information, a.k.a. fake news, which has become a serious threat to the credibility of politicians, organizations, and other decision makers. This paper proposes a framework for investigating the incentives to strategically spread fake news under different institutional configurations and payoff structures. In particular, we show under what conditions institutions that foster transparency in the media cause more fake news. Complementary, we study what kind of environments are particularly susceptible to the production of fake news.
Keywords: D72; D8; H0; L1; 330; campaigning; electoral competition; signal jamming; vertical product differentiation